Kegagalan Politik Multikulturalisme dan Pelembagaan Islamofobia di Negara-Negara Barat - Amin Nurdin (ILMU USHULUDDIN, 2015)
In the past decades, multiculturalism as a policy in Western Europe and in the United States of America was taken for granted as a kind of ‘success story’ for a ‘New World’ to replace the ‘Old World’ connotated with conservativism, racism and facism. But nowadays, new debates arise on the contestation between multiculturalism policy and terror attacts by certain radical groups on behalf of Islam. Muslims now are seen as potential threats for Western hegemony, and are considered not compatible with Western democracy values. Judging this, a question arises: is multiculturalism policy still need to be sustained? Is this an end or the failure of the multiculturalism ideology following the development of Islamophobia? This paper analyzes sources of the many success and failure factors in the practice of multiculturalism in the Western countries.